DAMPAK PROGRAM KELUARGA HARAPAN DI KECAMATAN KEMA KABUPATEN MINAHASA UTARA - WUMU, CAHYANI; LENGKONG, FLORENCE; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine The Impact of The Hopeful Outreach Program inKema District, North Minahasa Regency.This study uses a qualititave-descriptive approach. The Impact of The Family Program is seen from thefour effects of public policy proposed by James Anderson and by Thomas Dye. Research informants were 4family hope program participants, 2 community members were not participants of the hope family program,and assistants of the subdistrict hope family program. Data collection uses interview guidelines, while theanalytical technique used is the analysis of interactive models Miles and Hubernann.The result of the study how : (1) family planning programs have a positive impact on the families ofparticipants in improving the health status of family members, improving family/ child education, providingsocial walfare for poor families with severe disabilities and the elderly, helping to reduce family expensesand increasing income family, as well as changes in family behavior and independence. (2) hope familyprograms have a positive impact on people who are not the target group. (3) family planning programs alsohave a positive impact on the condition of society now. (4) family planning programs do not have an impacton the direct costs of the program and on the indirect costs that must be borne bythe community as a resultof the family hope program.This study recommends suggestions : (1) the determination of family program participants’ expectationsshould be done correctly/accurately in order to unsure that the hope family program participants really arepoor and vulnerable families; (2) large amounts of family program aid allowances for every poor familyshould not be thr same, but adjusted to the same, but adjusted to the number of family members who aredependent. (3) hope family program participants who do not comply whit the obligations of health andeducation requirement must be given strict sanctions.Keywords : Policies, Family Hope Programs.